2D/2D heterojunctions of WO3 nanosheet/K+Ca2Nb3O10− ultrathin nanosheet with improved charge separation efficiency for significantly boosting photocatalysis. Issue 16 (11th July 2017) - Ma, Xiaodong; Jiang, Deli; Xiao, Peng; Jin, Yu; Meng, Suci; Chen, Min
Abstract : Harvesting solar energy using semiconductor photocatalysts for wastewater decontamination offers a greener solution to address serious environmental crises. Abstract : Harvesting solar energy using semiconductor photocatalysts for wastewater decontamination offers a greener solution to address serious environmental crises. Delamination of layer photocatalysts into ultrathin two-dimensional (2D) nanosheets has induced fascinating properties such as electronic/protonic-conductivity and photocatalytic and fluorescent properties. K + Ca2 Nb3 O10 − is one prominent type of such materials, which is derived from the Dion–Jacobsen phase KCa2 Nb3 O10 by exfoliation. Here, a Z -scheme WO3 /K + Ca2 Nb3 O10 − binary 2D–2D heterojunction photocatalyst is successfully constructed through an easy hydrothermal coassembly method at room temperature. The as-synthesized WO3 /K + Ca2 Nb3 O10 − photocatalyst exhibited remarkable improvement in the photodegradation performance of tetracycline hydrochloride under simulated sunlight irradiation as compared to pristine WO3 and K + Ca2 Nb3 O10 − nanosheets. Sample 20%-WO3 /K + Ca2 Nb3 O10 − exhibited optimum efficiency, which is about 5.1-fold and 2-fold higher than those of WO3 and K + Ca2 Nb3 O10 −, respectively. Such an improvement is mainly related to its strongly coupled heterointerfaces, enlarged specific surface area and improved charge carrier separation and transfer. Radical capturing experiments and the spin-trapping ESR technique demonstrate that both ˙O2 − and h + are the important active species responsible for the tetracycline hydrochloride degradation process over the nanosheet heterojunctions.